Creating a Market for Skills Transfer: A Case Study of AVIC International's Skills Transfer Programs in Kenya - Irene Yuan Sun; Lin Qi (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2017)
This paper provides an in-depth case study of a set of local workforce development programs established by Chinese corporation AVIC International in Kenya. These programs' interesting characteristics challenge the stereotype that Chinese firms in Africa care little about local development. Although it is difficult to generalize from one example, AVIC's case has the potential to change our understanding of Chinese companies' contribution to skills development in Africa, showing at the very least that they can perceive such local investment as being in their self-interest. Chinese and African governments have expressed the desire for Chinese companies to do more in the area of skills transfer: AVIC's strategy, as one of the earliest and most prominent, may well offer a model for the future.
Keywords: 330